Governance Indicators - Kaufmann, Daniel; Kraay, Aart (World Bank, 2012)
Progress in measuring governance is assessed using a simple framework that distinguishes between indicators that measure formal rules and indicators that measure the practical application or outcomes of these rules. The analysis calls attention to the strengths and weaknesses of both types of indicators as well as the complementarities between them. It distinguishes between the views of experts and the results of surveys and assesses the merits of aggregate as opposed to individual governance indicators. Some simple principles are identified to guide the use and refinement of existing governance indicators and the development of future indicators. These include transparently disclosing and accounting for the margins of error in all indicators, drawing from a diversity of indicators and exploiting complementarities among them, submitting all indicators to rigorous public and academic scrutiny, and being realistic in expectations of future indicators.